Fresno County DSS Director Ben Kelley Retirement Dinner at Holiday Inn - Watkins, Howard::::::::: (1989)
Headtable all laughing: Vern Conrad, ?, Prudence Hutton, Dan Fitzpatrick, Ben Kelley and wife, Ramona Leila Hogner and Don Hogner